Myasthenia Gravis Coexisting With Primary Sjögren's Syndrome: Report of Three Cases and Literature Review - Li, Xia; Zhao, Yi; Liao, Qiuju; Da, Yuwei (Frontiers in Neurology, 2020)
Objective: The coexistence of myasthenia gravis (MG) and primary Sjögren's syndrome (pSS) is rarely reported. This study aims to describe the clinical features, treatment and outcome of MG coexisting with pSS. Materials and methods: Herein we reported 3 cases with the two coexisting diseases, and also searched the PubMed, Medline databases and China Wanfang databases for the relevant case reports written in English, Chinese or Japanese with detailed data. Results: We reviewed a total of 17 patients with both diseases. Fifteen patients were female. The median age at onset was 48 years (range 28 to 78 years). MG was the initial disease in nine of 17 cases. The median interval between the onsets of the two diseases was 30 months (range 7 months to 20 years). The symptoms of MG included fatigable ptosis (64.7%), bulbar symptoms (58.8%), muscle fatigability (64.7%), diplopia (64.7%), dyspnea (23.5%), and facial paralysis (5.9%). Anti-acetylcholine receptor antibody was positive in 70.6% patients. All the patients had sicca symptoms. Manifestations of pSS also included swollen exocrine glands (23.5%), joint pain (23.5%), hair loss (11.8%), leukopenia (11.8%), recurrent oral ulcers (5.9%), Raynaud phenomenon (5.9%), and fever (5.9%). ANA positivity was present in 70.6% patients, anti-SSA positivity in 47.1%, and double positivity of anti-SSA and anti-SSB in 17.6%. There were 12 patients (70.6%) with 2 autoimmune diseases (pSS and MG), and 5 patients with more than two autoimmune diseases. Cholinesterase inhibitors were the most commonly prescribed drugs (82.4%). Seven patients received thymectomy and 1 patient improved after the operation. Two patients were given intravenous methylprednisolone pulse therapy, and 4 patients oral steroids combined with immunosuppressants initially. Intravenous immunoglobulin and plasma exchange were used in 2 patients, respectively, for the respiratory failure. All the patients improved following treatment except one patient who died of MG crisis due to medication withdrawal. Conclusion: The coexistence of SS with MG is quite rare. The onset of MG may occur before or after the diagnosis of SS. Co-morbidity with MG does not seem to adversely affect the course of SS. Thus, controlling the progress of MG is the critical aspect of treatment.